Managing a Department of Obstetrics and Gynecology in Times of COVID-19 Outbreak: The Foch Hospital Experience - Murtada, Rouba; Carbonnel, Marie; Revaux, Aurélie; Favre-Inhofer, Angeline; Ayoubi, Jean-Marc (Frontiers in Surgery, 2021)
Departments of Gynecology and Obstetrics, as other departments, were faced with a major challenge at the outbreak of the COVID-19 pandemic. Fast restructuring was necessary in order to provide the means for COVID-related care. In this article we share our one-year experience in reshaping our activities, managing healthcare workers and securing a pathway for pregnant patients, including potential and confirmed COVID-19 cases. Priorities were set on ensuring patients’ and healthcare workers’ safety. Key containment measures included facemasks, systematic screening, dedicated spaces for COVID-19 cases with reinforced measures and vaccination campaign.